Croatia at the crossroads : a consideration of archaeological and historical connectivity : proceedings of conference held at Europe House, Smith Square, London, 24-25 June 2013 to mark the accession of Croatia to the European Union - Davison, David; Gaffney, Vincent L.; Miracle, Preston T.; Sofaer, Joanna R. (Archaeopress archaeology., 2016)
These papers focus on Croatia's particular interconnectedness in terms of social and cultural relationships with the wider region as the starting point for exploring issues across a broad chronological range, from human origins to modernity.